AYUAN BAGANDAI - Pransisko Pransisko; Herlinda Mansyur (SENDRATASIK UNP, 2019)
The dance "Ayuan Bagandai" aims to enjoy traditional dance in different forms without losing the traditional elements. The dancers work on the dance "Ayuan Bagandai" with a form of dance creation that is sourced from the traditional dance of the Muko-muko community, namely Gandai dance. The dancers tell how we keep the traditional dance is increasingly liked and known by many people. The dance "Ayuan Bagandai" is inspired by the phenomenon of the Muko-muko society, which nowadays, the majority of the people do not care about a traditional dance. When the era of dance increase and become an asset to the local area, it will gradually disappear without supporting of the society to preserve the dance. this phenomenon is seen by the dancers in Muko-muko District. They prefer to play modern dance, without realizing they want to eliminate the traditional dance that has grown within the society group.